A Method for Dynamic Response Analysis of Offshore Substation Platform Foundations Based on Modal Truncation - Jiefeng Chen; Hongchao Lu; Enjin Zhao (Journal of Marine Science and Engineering)
The foundation structure of offshore substation platforms is complex and has numerous degrees of freedom. The computational efficiency of dynamic response analysis using traditional time-domain methods is often relatively low. To facilitate the dynamic response analysis of offshore substation platform foundation structures with large degrees of freedom (DOFs), this paper proposes a method for dynamic response analysis based on modal truncation, which involves conducting a modal analysis and decoupling the vibration system matrix based on the modal shapes. Additionally, it analyzes the external load spectrum and determines the modal-truncation range through the transfer relationship between the external load frequency and the modal response. This approach reduces the size of the dynamic response analysis matrix, thereby significantly improving the computational efficiency of the dynamic response analysis of large-DOF offshore substation platform foundations. A six-DOF mass-damping-spring system and a finite element model of an offshore substation platform foundation were used to test the proposed method. The proposed method reduces the number of decoupled equations used to analyze the offshore substation platform foundation from 312 to 9. It was compared with the Newmark-β method, and the results show that the proposed method aligns well with the Newmark-β method in terms of calculation results, with computational efficiency improved by approximately 100 times.